Students Responses toward Fix-Up Options Strategy Implementation in Comprehending Text Personal Recount - Jannah, Raudhatul; A. Gani, Sofyan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aimed to figure out students' responses toward using the fix-up options strategy in comprehending text personal recount. The qualitative method was used to collect the data. The sample was the second grade of Pos Keadilan Peduli Ummat (PKPU)Â junior high school students, which consisted of 22 students. The open-ended questionnaire was distributed as the instrument for collecting the data. It consists of three questions that relate to studentsâ€™ opinions on this strategy. The data was analyzed by using an interactive model. The result of this study indicated that there were positive responses from the students toward fix-up options strategy implementation in comprehending personal text recount. Most students consider this strategy beneficial in supporting their comprehension of reading a text. The students' opinions were categorized into agreeing and disagreeing group participants. The fix-up options strategy was useful in fixing the problem encountered during the reading process. Therefore, the teacher could use this strategy to support students' reading comprehension in other genres of text.